2010
DOI: 10.2174/092986710790820651
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Biological Markers of Frontotemporal Lobar Degeneration Spectrum

Abstract: In the last decade, there has been enormous progress in our understanding of Frontotemporal Lobar Degeneration (FTLD). Published clinicopathological series have clearly demonstrated an overlap between the clinical syndromes subsumed under the term frontotemporal dementia and the Progressive Supranuclear Palsy (PSP), and the Corticobasal Degeneration (CBD) syndrome. From a neuropathological point of view, two broad pathological subdivisions of FTLD are currently recognized: a) tau-positive pathology due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In FTLD, reports of CSF tau levels have been widely variable [6][7][8], but the meaning of such a finding needs to be further elucidated. The results of the present work suggest that CSF tau might be considered a marker of neurodegeneration, and higher levels of tau protein in CSF might be associated with increased vulnerability of specific brain areas, thus leading to defined neuropsychological deficits and brain atrophy pattern as compared to patients with lower CSF tau.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In FTLD, reports of CSF tau levels have been widely variable [6][7][8], but the meaning of such a finding needs to be further elucidated. The results of the present work suggest that CSF tau might be considered a marker of neurodegeneration, and higher levels of tau protein in CSF might be associated with increased vulnerability of specific brain areas, thus leading to defined neuropsychological deficits and brain atrophy pattern as compared to patients with lower CSF tau.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clear-cut neuroimaging features, affecting frontal and temporal lobes [3], no diagnostic biological markers are available yet. Several studies have evaluated the usefulness of cerebrospinal fluid (CSF) total tau and phospho-tau levels in patients with FTLD, but with contrasting findings [4][5][6][7][8]. Indeed, while it has been widely demonstrated that CSF tau, phospho-tau, and amyloid-␤ (A␤) markers are reliable tools to identify Alzheimer's disease in the preclinical stages [9][10][11], in FTLD, the results have been highly variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hexanucleotide repeat expansions (GGGGCC) in a non-coding region of C9orf72 are the most common genetic abnormality in both ALS and FTD, which is responsible for approximately 40% of familial ALS, 5–10% of sporadic ALS, 40% of familial FTD, and 4–21% of sporadic FTD [ 13 , 14 , 15 ]. Mutations in the genes encoding the TAR-DNA binding protein (TDP-43) ( TARDBP ), fused in sarcoma (FUS) ( FUS ), TANK-binding kinase-1 ( TBK-1 ), Ubiquilin 2 ( UBQLN2 ), optineurin ( OPTN ), and Cyclin F ( CCNF ), are also present in both ALS and FTD patients [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. In contrast, mutations in other genes are present in ALS only, including SOD1 and VAPB, encoding superoxide dismutase 1 and VAMP (vesicle-associated membrane protein)-associated protein B and C, respectively [ 32 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Thus, one current major problem is the overlapping neuropathology and the as yet incompletely understood molecular constituents of the pathological changes. It is expected that in the next years many more neuropathological entities will be identified and characterized at the molecular level, which will also influence our thinking of clinical phenotyping and the selection of biomarker candidates in the future [ 25 ].…”
Section: Introductionmentioning
confidence: 99%